Insights from DEspR-deficiency and haploinsufficiency - Herrera, Victoria L.M. (2009)
We recently showed that DEspR-haploinsufficiency resulted in increased neuronal autophagy and spongiform changes in the adult brain especially the hippocampus, cerebral cortex and basal ganglia, causing cognitive performance deficits. This model demonstrates a causal link between increased autophagy and neurodegenerative changes. This is in contrast with recent observations that decreased autophagy from null mutations of autophagy genes, Atg5 and Atg7, results in early neurodegenerative changes. With the observed autophagy phenotype, we then compared the neural tube phenotype of DEspR-deficient mice with knockout mice of genes established to underlie or regulate autophagy. Intriguingly, the hyperproliferative neuroepithelium observed in DEspR-deficient embryos is also detected in null mutants of Ambra1, an autophagy modulator, and two apoptosis genes, Apaf1 and Caspase 9. While all four knockout models exhibited hyperproliferative neuroepithelium, DEspR-deficient mice differed by having greater neural tube cavitation. Additionally, observed DEspR roles in angiogenesis and autophagy recapitulated the association of angiogenesis inhibition and increased autophagy as observed for endostatin and kringle5, thus elucidating an expanding complex network of autophagy, apoptosis and angiogenesis in neuroepithelial development, and an emerging complex spectrum of autophagy effects on neurodegeneration. Nevertheless, DEspR provides a ligand-activated receptor system to modulate autophagy—be it to increase autophagy by inhibition of DEspR-function, or to decrease autophagy by agonist stimulation of DEspR-function.